Réduction Electrochimique du Bioxyde de Carbone en Solution Aqueuse - Jan Augustynski (CHIMIA)
The reduction of carbon dioxide requires a substantial input of energy or a high energy reductant. Among possible energy sources which may be used to drive this reaction are electricity and light. First approaches to the electrochemical reduction of carbon dioxide in aqueous solutions are as old as the very beginning of interest in electrochemical processes. During several years, the cathodic reduction of carbon dioxide appeared as a highly irreversible reaction, restricted to the formation of formic acid. As will be shown in the present article, these views are to be re-examined in the light of the results of recent studies, showing that several electrode materials enable the reduction of carbon dioxide to occur with small or moderate overvoltages and to yield a large variety of products.